2018
DOI: 10.1016/j.foodres.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical and bioactivity profiles of wild Calluna vulgaris L. flowers

Abstract: The nutritional composition of Calluna vulgaris flowers as well as the phytochemical profile, antioxidant (DPPH and FRAP assays), antimicrobial and cytotoxic (in human immortalized non-tumorigenic keratinocyte and fibroblasts) activities of aqueous, hydroalcoholic and ethanolic extracts were evaluated. A high content of fiber and carbohydrates (75%) and the prevalence of α-tocopherol as vitamer deserves attention. Linolenic (35%), linoleic (27%) and palmitic (21%) acids were the most abundant fatty acids. Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…Carbohydrates were the most abundant macronutrients (83.1 ± 0.3 g per 100 g dw), followed by proteins (8.4 ± 0.3 g per 100 g dw), lipids (4.42 ± 0.04 g per 100 g dw), and ashes (2.3 ± 0.04 g per 100 g dw). These results are in agreement with Rodrigues et al, 31 who evaluated the nutritional composition of the wild flowers of C. vulgaris and also identified carbohydrates in higher amounts (36.2 ± 0.2 g per 100 g dw), followed by proteins (6.8 ± 0.27 g per 100 g dw), lipids (3.7 ± 0.1 g per 100 g dw), and ashes (2.3 ± 0.04 g per 100 g dw). Fructose and glucose were the two identified sugars, glucose being present in higher amounts (5.36 ± 0.08 g per 100 g dw).…”
Section: Nutritional Compositionsupporting
confidence: 94%
“…Carbohydrates were the most abundant macronutrients (83.1 ± 0.3 g per 100 g dw), followed by proteins (8.4 ± 0.3 g per 100 g dw), lipids (4.42 ± 0.04 g per 100 g dw), and ashes (2.3 ± 0.04 g per 100 g dw). These results are in agreement with Rodrigues et al, 31 who evaluated the nutritional composition of the wild flowers of C. vulgaris and also identified carbohydrates in higher amounts (36.2 ± 0.2 g per 100 g dw), followed by proteins (6.8 ± 0.27 g per 100 g dw), lipids (3.7 ± 0.1 g per 100 g dw), and ashes (2.3 ± 0.04 g per 100 g dw). Fructose and glucose were the two identified sugars, glucose being present in higher amounts (5.36 ± 0.08 g per 100 g dw).…”
Section: Nutritional Compositionsupporting
confidence: 94%
“…In addition, it was previously shown that the basic BASs of C. vulgaris are phenols and their glycosides (hydroquinone, arbutin and methylarbutin), hydroxycinnamic acids, coumarins, flavonoids (kaempferol, quercetin, astragalin, hyperoside, herbacetin, luteolin and isoquercetin), tannins and their metabolites, and terpenes (α-pinene and β-pinene) [ 12 , 13 , 14 , 15 ]. It is a valuable source of BAS that has anti-inflammatory, antibacterial, sedative and anti-anxiety activities [ 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the flavonoids in heather plants are representatives of subclasses, such as flavonols, dihydroflavonols, flavones and isoflavones, flavonones, chromones, catechins, tannins, proanthocyanidins, and anthocyanins [18]. The most distinct flavonoids of heather are quercetin and its glycosides alongside callunin and kempferol-3-β-D-galactoside [19]. It should be noted that, in addition to phenolic compounds in the leaves and flowers of heather, terpenoids (lupeol, ursolic, and oleanolic acids) have been identified and determine the antitumor effect of heather extracts, as well as organic acids (ascorbic, oxalic), β-carotene (provitamin A), and steroids [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the phytochemical composition of heather is quite well researched [ 12 , 16 , 17 , 18 , 19 , 29 , 30 ], studies on the change in content of the phenolic compounds in various plant organs (leaves, stems, roots, rhizomes, flowers, and seeds) at various stages of ontogenesis did not take place previously. The authors of the studies available to date researched either the seasonal variation in phenolic compound content in a whole aerial part of the plant or in various organs of the plant at one vegetation phase (mainly at the flowering stage).…”
Section: Introductionmentioning
confidence: 99%